PERAN GANDA JANDA DALAM BERTAHAN HIDUP DI KELURAHAN BALANG BERU KECAMATAN BINAMU KABUPATEN JENEPONTO: PERAN GANDA JANDA DALAM BERTAHAN HIDUP - NIMRUNG, MUSTIKA; MANDJARREKI, SAKARUDDIN; ANDI MUH. FADLI (Jurnal Washiyah, 2026)
This study, entitled “The Dual Roles of Widows in Sustaining Livelihoods in Balang Beru Sub-District, Binamu District, Jeneponto Regency,” aims to explore the economic activities undertaken by widows to maintain their livelihoods and to analyze government programs designed to support their welfare. This research employed a qualitative approach grounded in post-positivist philosophy with a descriptive design. Primary data were collected through in-depth interviews and direct observation with informants in the field, while secondary data were obtained through documentation. The findings indicate that widows in Balang Beru Sub-District perform dual roles in their daily lives. They manage to sustain their livelihoods through various economic activities despite limited resources and rely on social assistance programs provided by the government to improve their welfare. These assistance programs serve as essential support mechanisms that help mitigate the economic challenges faced by this vulnerable group. This study implies the need for continuous attention from local governments, especially in Binamu District, to address the needs of economically disadvantaged widows. It is recommended that policies be strengthened to ensure the sustainability of assistance and empowerment efforts for these women. Furthermore, widows are expected to fulfill their parenting roles responsibly and prioritize their primary obligations to their families.